HUBUNGAN ANTARA KONSEP DIRI DENGAN PERILAKU PROSOSIAL - I Made Mahaardhika (Widyadari : Jurnal Pendidikan, 2019)
This study aims to determine whether there is a relationship between self-concept and student prosocial behavior. The population of this research is 10 SMA 4 Denpasar students. While the number of research samples is 280 people. The sampling technique used is Stratified Proportional Random Sampling. In collecting data using a questionnaire method with a Likert model measurement scale. Based on the results of the analysis conducted, the results of the study are significant. The amount of the null hypothesis rejection limit value obtained in the Product Moment value table is 0.113. When compared with the value of the research results obtained by 0.649 then the value of the results of the study is above or greater than the value of the null hypothesis rejection limit obtained from the table, so the proposed null hypothesis is rejected so that this research can be said to be significant.